FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA APLIKASI PESAN ANTAR MAKANAN DI JAKARTA - Inna Hanarti; May Vitha Rahmadhani; Edi Wahyu Wibowo; Minggu Minggu (POLITEKNIK LP3I JAKARTA, 2021)
Digital businesses are starting to grow, including the food ordering business where we can order food using applications available on smartphones. Ordering food can be done from anywhere and anytime, without having to come to the store or to the mall directly. This research is quantitative with 144 respondents. The results of this study state that the variable of consumer attitudes partially has a positive effect on purchasing decisions. Even though the results of this study are good, it is better for the delivery service application providers to provide member loyalty programs, so that consumers will continue to use this application. For consumer motivation variable partially positive influence on purchasing decisions. Even though the results of this study are good, it is better for the delivery service application providers to provide a discount program so that consumers are motivated to always use this delivery application. For the consumer perception variable, it partially has a positive effect on purchasing decisions, although the results of this study are good, it is better for the delivery service application providers to provide CSR or Corporate Social Responsibility programs so that this delivery application has a good perception in the hearts of consumers. For Attitude, Motivation Variables and Consumer Perceptions have a simultaneous effect on purchasing decisions. Even though the results of this study are good, it is better for the delivery service application providers to provide relationship marketing programs, especially after-sales services, so that consumers are very happy to use this delivery application.Keywords: Delivery Application, Purchase Decision, Consumer Attitude, Purchase Motivation